RANCANG BANGUN PROTOTIPE MONITORING PENGAIRAN SAWAH BERBASIS LORA RA-02 SX1278 - Zamani Noor, Z; Semara Putra, I G A Anom; Saputra, KO; Dewi Wirastuti, NMAE (Jurnal SPEKTRUM, 2022)
Rice field irrigation is still done manually by farmers in opening and closing waterways, so it takes farmers time to manage waterways. In this study, a system was created with two types of devices, namely the sender and the receiver. The sending device consists of ArduinoUNO, Soil Moisture Sensor, Water Level Float Switch, and LoRa Ra-02 SX1278. Then, the receiver consists of NodeMCU ESP8266, LoRa Ra-02 SX1278, Relay, Water Pump. After testing, the system can send notifications to the user when the rice fields are dry or the rice fields are full, the pump can automatically turn on and turn off and the user also can turn the pump on or off via Telegram Bot. User can also command the device to operate automatically via Telegram Bot.